Analysis of metric and descriptive traits of human auricle as performed on plaster casts - Klonowska, Ewa (Anthropological Review, 1978)
The aim of this paper is to evaluate usefulness of plaster casts of auricles for anthropometric examination as well as for elaborations of practical significance. Simultaneously the author attempted to observe age variability of auricle in males and females. The material consisted of casts of right and left auricles prepared in Dental School at Szczecin, Casts of 265 individuals of both sexes aged 16-50 years were used for the present work, Following characters were observed on casts: 1, physiognomic length, (sa-sba), 2. physiognomic width (pra-pa), 3. lobe length (sba-inc), 4. physiognomic width of the cartilage (sa-inc) and ear conche, 5. projected length measured to inc, 6. projected width, 7. maximum projected length, and 8. maximum projected width, plus five descriptive traits. Measurements 7 and 8 were taken perpendicularly one to the other. Observed characters were analysed with respect to sexual dimorphism, asymmetry and changes with age by means of computing arithmetic means. Significance of differences between compared means was tested by means of Student’s t-test. Results obtained are as follows: measurements taken on casts are noticeably different from those taken on auricles quoted in the literature. Measurements of auricle and ear conche are highly correlated. Values of the majority of measurements are higher in males. Analysis revealed no consistent asymmetry. Age changes are slight. Formation and variability of analysed descriptive traits are similar to those observed in other samples of Polish population.